Conversational implicature and cooperativeness in D.H Lawrence's sons and lovers / Angelina Subrayan Michael and Chittra Muthusamy - Michael, Angelina Subrayan; Muthusamy, Chittra (Universiti Teknologi MARA, Kedah, 2015)
This study examines the conversational implicature and the use of cooperative principles in the novel Sons and Lovers (1913) by D.H. Lawrence (Lawrence). Men and women inhabit different worlds, which gives rise to differentiated meanings attached to words. There is a significant interest in the pragmatic variation linked with the speakers in the novel. Research conducted to date in anthropology and education clearly states that conversational implicature and cooperativeness in utterances are important social variables that should be analysed through the most common cultural codes of society, which is its language. The purpose of this study is to identify the types of conversational implicature and the cooperative principles used in various relationships in the text and the reason behind its use during the industrialisation era in the novel. The selected utterances from the novel are analysed using Gricean cooperative maxims which are then related to the social norms during the industrialised era in the novel. This study allows readers to understand the rules governing successful conversational interaction. The findings show that the success of a conversation depends upon the various speakers' approach to the interaction. In the novel, conversational implicature among the characters gives immense meaning with virtually little actual speech.